Review of W. Heckel, In the Path of Conquest. Resistance to Alexander the Great, Oxford, Oxford University Press (2020) - Raúl Navas-Moreno (Karanos)
Review of Waldemar Heckel, In the Path of Conquest. Resistance to Alexander the Great, Oxford, Oxford University Press (2020).